Training English language pre-service teachers using a team based learning approach - Abd. Samad, Arshad; Husein, Hawanum; Md. Rashid, Juridah; Syd Abd. Rahman, Sharifah Zainab (Canadian Center of Science and Education (CCSE), 2015)
Team Based Learning which focuses on enhancing positive group dynamics is a relatively popular instructional approach in several disciplines such as Health Sciences and Business but has yet to gain popularity in Education. This paper examines the use of Team Based Learning in teacher training as well as the receptiveness towards the approach as indicated by a group of Teaching English as a Second Language teacher trainee. The trainees were asked to write diaries regarding their experiences working in a team during a course for a semester which were then collected in three cycles throughout the semester. Entries were analysed in terms of whether there were positive, negative or neutral reference to working in teams. All members of a team were also required to participate in individual micro teaching sessions for which they were evaluated. Findings indicate that Team Based Learning has a potential role in teacher training as positive entries outnumbered negative entries. Additionally, teams with high average micro teaching scores also had more positive diary entries.